Periodontal stability and treatment needs in patients under antiresorptive therapy during supportive periodontal care: a retrospective case-control study - Ciardo, Antonio; Simon, Marlinde M.; Rosse, Hanna-Sophie; Awounvo Awounvo, Junior Sinclair; Kim, Ti-Sun (Quintessence international, 2025)
This study aimed to investigate periodontal stability and treatment needs in patients under antiresorptive therapy (ART) during supportive periodontal care (SPC), with a focus on medication-related osteonecrosis of the jaw (MRONJ) risk and reasons for tooth loss. Method and materials: In this retrospective case-control study, records of 100 stage III/IV SPC patients (50 ART-exposed, 50 unexposed) were analyzed for probing pocket depth, clinical attachment level, bleeding on probing, history of periodontal surgery, tooth loss, and MRONJ risk over a period of up to 15 years after active periodontal therapy.
Gesehen am 12.08.2025